Flavonoids from Litsea japonica Inhibit AGEs Formation and Rat Lense Aldose Reductase In Vitro and Vessel Dilation in Zebrafish - Lee, Ik-Soo; Kim, Yu Jin; Jung, Seung-Hyun; Kim, Joo-Hwan; Kim, Jin Sook (Planta Medica, 2017)
In our ongoing efforts to identify effective naturally sourced agents for the treating of diabetic complications, two new (1 and 2) and 11 known phenolic compounds (3–13) were isolated from an 80 % ethanol extract of Litsea japonica leaves. The structures of the new compounds were established by spectroscopic and chemical studies. These isolates (1–13) were subjected to an in vitro bioassay evaluating their inhibitory activity on advanced glycation end products formation and rat lens aldose reductase activity. Of the compounds evaluated, the flavonoids (3, 4, 6–8, 11, and 12) markedly inhibited advanced glycation end products formation, with IC50 values of 7.4–72.0 µM, compared with the positive control, aminoguanidine (IC50 = 975.9 µM). In the rat lens aldose reductase assay, consistent with the inhibition of advanced glycation end products formation, the flavonoids (3, 4, 6–8, 11, and 12) exhibited considerable inhibition of rat lens aldose reductase activity, with IC50 values of 1.1–12.5 µM. In addition, the effects of kaempferol (4) and tiliroside (7) on the dilation of hyaloid-retinal vessels induced by high glucose in larval zebrafish were investigated. Only kaempferol significantly reduced the diameters of high glucose-induced hyaloid-retinal vessels, by 52.2 % at 10 µM, compared with those in the high glucose-treated control group.
Keywords: Litsea japonica; Lauraceae; advanced glycation end-products; rat lens aldose reductase; zebrafish; diabetic vascular complications